Daya Antibakteri Berbagai Konsentrasi Ekstrak Daun Kembang Bulan (Tithonia Diversifolia (Hemsl.) A. Gray) Terhadap Bakteri Porphyromonas Gingivalis Dominan Periodontitis (In Vitro) - Koptaria, Andini, drg. Soetomo Nawawi, DPH.Dent,Sp.Perio (K), drg. Juwita Raditya Ningsih (2015)
Porphyromonas gingivalis bacteria were the prominent pathogen that contributed on initiation and progressiveness of periodontal disease. Mary gold leaves extract could be considered as antibacterial essence because it's contained alkaloid, tannin, flavonoid, terpenoids and saponins. Theory of this study was to find out antibacterial Properties of various concentration of mary gold leaves (Tithonia diversifolia (Hemsl.) A. Gray) extract against Porphyromonas gingivalis. The mary gold leaves were being extracted by maceration technic using 70% ethanol solution. After 5%, 10%, 20%, 40%, 80% consentrations of mary gold extract were ready, it were then registered on disk diffusion susceptibility test (Cups Plate). Aquadest used as negative control and metronidazol gel used as positive control in this research. . Data were analized using one-way ANOVA test, followed by Post Hoc LSD test to determine the significant differences between treatment groups. The result showed p = 0.000 which means that various concentrations of mary gold leaves extract have significant effect to inhibit Porphyromonas gingivalis. The result of Post hoc LSD indicate that there were significant differences on positive control and metronidazole gel's means with various concentrations of mary Gold leaves extract.